Learning about Students’ Receiving Special Educational Support Experiences of Qualification, Socialization and Subjectification in Finnish Vocational Education and Training: A Narrative Approach - Ryökkynen Sanna; Maunu Antti; Pirttimaa Raija; Kontu Elina K (MDPI, 2022)
This paper airs the experiences of eighteen students with special educational needs completing their studies at a Finnish vocational institution, which has a mandate to provide intensive special support for the students. It contributes to the national and international discussion of education’s purposes and elaborates on students’ descriptions. The study frames a research question: To what extent are Biesta’s domains of good education—qualification, socialization, and subjectification—audible in the narratives of Finland’s VET special educational needs students? The paper adopts a narrative approach and uses narrative positioning analysis as a methodical tool to drill down into the themes produced in deductive content analysis. According to our analysis, subjectification and socialization were the most important domains of VET. The qualification domain of education did not appear as professional self-confidence in students’ narratives, but it served as subjectification and socialization. VET must be an inclusive process that provides all students with the opportunity to become balanced and civilized citizens and assist them in entering the world. To this end, instead of emphasizing measurable outcomes such as qualifications and employment rates, more attention should be paid on the social and subjective domains of VET.